Back Cover: The Role of Hydroxyl Group Acidity on the Activity of Silica‐Supported Secondary Amines for the Self‐Condensation of n‐Butanal (ChemSusChem 3/2015). Issue 3 (27th May 2014) - Shylesh, Sankaranarayanapillai; Hanna, David; Gomes, Joseph; Canlas, Christian G.; Head‐Gordon, Martin; Bell, Alexis T.
<x xml:space="preserve">Abstract</x> The Back Cover picture shows the utility of mesoporous silica‐supported secondary amine catalysts for the sustainable production of diesel fuel or additives from biomass‐derived platform molecules. As fermentation products possess lower carbon numbers coupling chemistry is needed to design larger molecules. To realize selective coupling, we developed a highly efficient solid‐base organocatalyst for the self‐condensation of n‐butanal to 2‐ethylhexenal by grafting site‐isolated amines on tailored silica surfaces. The spacing between the amines and M‐OH groups (M=Al, Ti, Zr, Sn) is crucial to maximize their co‐operative action and to minimize acid–base neutralization. The catalytic activity can be significantly altered by controlling the Brønsted acidity of the M‐OH species. More details can be found in the Full Paper by Shylesh et al. on page 466 (DOI: 10.1002/cssc.201402443).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>